2017
DOI: 10.1155/2017/2563910
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of MRE11 and Clinicopathologic Characteristics in Recurrence of Breast Cancer: Individual and Cumulated Receiver Operating Characteristic Analyses

Abstract: The interaction between the meiotic recombination 11 homolog A (MRE11) oncoprotein and breast cancer recurrence status remains unclear. The aim of this study was to assess the interaction between MRE11 and clinicopathologic variables in breast cancer. A dataset for 254 subjects with breast cancer (220 nonrecurrent and 34 recurrent) was used in individual and cumulated receiver operating characteristic (ROC) analyses of MRE11 and 12 clinicopathologic variables for predicting breast cancer recurrence. In individ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Relatively, heterozygous mutation only contributes a limited fraction of tumorigenesis, and aberrant molecular variation of MRN is more frequent and of great clinical significance 21, 22. Previous studies had reported the role of MRE11 in cell survival and proliferation 23, and malignant cancer behavior was significantly correlated with elevated MRE11 expression phenotypes in breast 19, 24, 25, gastric 26 and rectal cancer 27, 28. Similarly, it was noteworthy that increased recurrence rate and chemoresistance of certain cancers correlated with high expression level of MRN complex 28-30.…”
Section: Discussionmentioning
confidence: 99%
“…Relatively, heterozygous mutation only contributes a limited fraction of tumorigenesis, and aberrant molecular variation of MRN is more frequent and of great clinical significance 21, 22. Previous studies had reported the role of MRE11 in cell survival and proliferation 23, and malignant cancer behavior was significantly correlated with elevated MRE11 expression phenotypes in breast 19, 24, 25, gastric 26 and rectal cancer 27, 28. Similarly, it was noteworthy that increased recurrence rate and chemoresistance of certain cancers correlated with high expression level of MRN complex 28-30.…”
Section: Discussionmentioning
confidence: 99%
“…ROC analysis is also used to evaluate the accuracy of various biomarkers for diagnosis, prognosis and survival predictions for cancer patients [ 24 31 ]. Recently, ROC analysis has been improved by simultaneously considering multiple factors in terms of cumulative ROC analysis [ 32 34 ].…”
Section: Introductionmentioning
confidence: 99%